Circulating YKL-40 in Philadelphia-negative myeloproliferative neoplasms. Issue 1 (2nd January 2021) - Krečak, Ivan; Gverić-Krečak, Velka; Lapić, Ivana; Rončević, Pavle; Gulin, Josipa; Fumić, Ksenija; Krečak, Filip; Holik, Hrvoje; Duraković, Nadira
ABSTRACT: Objectives: Philadelphia-negative chronic myeloproliferative neoplasms (MPNs), essential thrombocythemia (ET), polycythemia vera (PV) and myelofibrosis (MF), are characterized by clonal myeloproliferation and a strong inflammatory atmosphere. YKL-40, expressed in granulocytes, macrophages, megakaryocytes and malignant cells, is an acute phase reactant with an important role in tissue remodeling and atherosclerotic inflammation. The aim of this study was to investigate serum YKL-40 levels in MPNs and to assess its clinical correlations. Methods: ELISA test was used to measure serum YKL-40 levels in 111 MPN patients and in 32 healthy controls. Results: Serum YKL-40 levels were higher in ET, post-ET MF, PV, post-PV MF and primary MF patients, when compared to healthy controls (p < 0.001). Higher serum YKL-40 levels were associated with parameters indicative of the increased inflammatory state (higher C-reactive protein, poor performance status, presence of constitutional symptoms and cardiovascular risk factors). Additionally, higher serum YKL-40 levels in MF patients were associated with blast phase disease, lower hemoglobin and higher Dynamic International Prognostic Scoring System score. In the multivariate Cox regression models, higher serum YKL-40 levels in ET and PV patients were independently associated with an increased risk of thrombosis (HR 4.64, p = 0.031) and impaired survival in MF patients (HR 4.31, p = 0.038). Conclusion: These results indicate that higher circulating YKL-40 levels in MPNs might have a pathophysiological role in disease progression and thrombosis development. Assessing circulating YKL-40 could help in identification of ET and PV patients at a high risk of future cardiovascular events and has a good potential for improving prognostication of MF patients.